The CORRELATION BETWEEN PRODUCTIVE AND RECEPTIVE LANGUAGE SKILLS: AN EXAMINATION ON ADFELPS TEST SCORES: An Examination on ADFELPS Test Scores - Ella Yuzar; Siti Rejeki (SALEE: Study of Applied Linguistics and English Education, 2020)
Abstract ADFELPS Tests has been widely used as a predictive test to help stakeholders in making decisions in levelling Indonesian defence attachés’ English proficiency before they are assigned abroad. Despite the significant demands in examining the test for the purpose of informing the test users about the army officers’ English competence, little research has attempted to evaluate this standardized test. The present study, therefore, aimed to analyse the connection between the receptive and productive language skills of the test. Besides, it is also keen to explore whether test takers’ age, frequency of test-taking and length of study affect their scores and which part of the test is the most difficult to complete. Thirty military officers participated by submitting their ADFELPS Test scores and answered a designed questionnaire. IBM SPSS 2.5 software was used to perform a variety of analysis procedures such as the Pearson correlation analysis, an Analysis of Variance (ANOVA) and an independent t-test procedure. It revealed a strong relationship between ADFELPS test score of language receptive skills (listening and reading) and the productive skills (speaking and writing) and listening is the dominant skill that correlates with all other language proficiency skills. Second, listening skill is particularly considered as the most difficult skill to acquire due to its complexity in the language learning process. Finally, participants’ age and their experiences of taking the test do not bring a significant impact on the improvement of ADFEPLS achievement score. In contrast, length of study preparation has helped test takers in increasing their test scores.